A Systematic Literature Review of Financial Sustainability - Ni Luh Gde Novitasari; I Ketut Yadnyana; Gayatri Gayatri; I Nyoman Wijana Asmara Putra (Indonesian Journal of Sustainability Accounting and Management, 2024)
This study aims to examine the progression of financial sustainability by conducting a systematic literature review. It involves critical evaluations of prior research endeavors and endeavors to pinpoint potential directions for future analyses. The data were analyzed using a qualitative approach, which involved examining 27 articles published between 2013 and 2022. Certain reviews have adopted a quantitative method, primarily focusing on microfinance institutions and banks, there has been limited discourse on the implementation of financial sustainability in both the private and public sectors. The results of this research offer a thorough examination of the development of financial sustainability over the past decade. The conducted review addresses a gap in the existing literature and acts as a valuable roadmap for future investigations into financial sustainability. This research fills a critical gap in existing literature and lays the groundwork for future investigations. Its implications extend to informing decision-makers, practitioners, and policymakers, emphasizing the need for a holistic approach in comprehending the multifaceted aspects of sustainable financial practices. The value of the study is offering a nuanced perspective that bridges a gap in existing literature. The findings contribute to informed decision-making for practitioners, policymakers, and academics, fostering a holistic approach to sustainable financial practices.